Exploring the mechanical performance of BaTiO3 filled HDPE nanocomposites: A comparative study of the experimental and numerical approaches. (21st July 2022) - Atli, Atilla; Noyel, Jean-Philippe; Hajjar, Ahmad; Antouly, Kevin; Lemaire, Etienne; Simon, Sandra
Abstract: The mechanical behavior of BaTiO3 incorporated High-Density Polyethylene (HDPE) nanocomposites up to 40% in volume is investigated experimentally through tensile tests. The results showed that Young's modulus increased with increasing amount of BaTiO3 particles, indicating a higher stiffness. A numerical approach based on a micromechanical model showed the same trend, but with values lower than the experimental ones for all the composite concentrations. The influence of the particle distribution (uniform or random) in the Representative Volume Element (RVE) as well as the RVE size were particularly investigated. The effect of the strain and strain rate on the Young's modulus was highlighted experimentally and numerically. The influence of the filler particles on the strain and stress field distributions in RVE was shown to be a key parameter in the mechanical response of the nanocomposites and revealed the necessity to take into account the true behavior of HDPE in the numerical modeling. Graphical abstract: Image 1 Highlights: Numerical approach to understand the modification of mechanical properties of barium titanate filled HDPE. Influence of filler particles on Young's modulus of composites studied by experimental and numerical approaches. True mechanical behavior of HDPE in the HDPE matrix composites. Focus on the strain and strain rate on the mechanical properties of the BaTiO3 -HDPE nanocomposites. Emphasizing on the stress and strain field distributions on the mechanical behavior of composites emphasized by numerical approach.